If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(2x + -3) = 2x + 12 Reorder the terms: 7x + -1(-3 + 2x) = 2x + 12 7x + (-3 * -1 + 2x * -1) = 2x + 12 7x + (3 + -2x) = 2x + 12 Reorder the terms: 3 + 7x + -2x = 2x + 12 Combine like terms: 7x + -2x = 5x 3 + 5x = 2x + 12 Reorder the terms: 3 + 5x = 12 + 2x Solving 3 + 5x = 12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 5x + -2x = 12 + 2x + -2x Combine like terms: 5x + -2x = 3x 3 + 3x = 12 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 3x = 12 + 0 3 + 3x = 12 Add '-3' to each side of the equation. 3 + -3 + 3x = 12 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = 12 + -3 3x = 12 + -3 Combine like terms: 12 + -3 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| -3y-8=2y+22 | | -10f=-9f-7 | | 3(d+12)=a-4d | | 2ab+a=300 | | 8n-6-4n=4n-6 | | 7(x-4)=2(x+3)+x+2 | | -2(3x-5)+4=-6x+14 | | .005ab+a=300 | | 9a+5b+7a+8b=0 | | 8x*12x= | | 15+n=n-15 | | 2ab+b=300 | | 7y+4(y-8)=3(y+1)-2 | | 2x+y=-83 | | 3z-18=15-5z | | -12+13=10+n | | x^2+dx+49=0 | | 36x^2+17x-35=0 | | 4+w=3 | | F(X)=7x^8-1x^4+1 | | 84=12s | | -w+2=-2w+7 | | -3x-7x=-12 | | -2+15=4b-4-3b | | 20+m+13+m=2 | | -5a+24+2a=7a-4a | | (8+5i)(2-5i)= | | X+12-(-4)=17 | | 12-2(x+1)=5 | | 8-3x+12=11 | | 0.3x-0.7x-27=1 | | 6x+10038=x-28483 |